GAMBARAN KEPATUHAN MINUM OBAT PENCEGAHAN MASSAL FILARIASIS (STUDI DI WILAYAH KERJA PUSKESMAS JETAK KABUPATEN SEMARANG - Putri Ratna Sari; Praba Ginandjar; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2020)
Coverage of filariasis’ Mass Drug Administration at Jetak Public Health Center in the second round of treatment decreased from 99.6% to 77.2%. This shows the decrease in community participation in joining the filariasis’ MDA. The purpose of this study is to describe drug compliance of filariasis’ MDA in the working area of Jetak Public Health Center, Semarang Regency. This research is a descriptive cross sectional study using the rapid survey method. The study population is the entire target population for the second round of filariasis’ MDA in 2018 in the working area of the Jetak Community Health Center, aged ≥ 18 years. The sample size is 210 respondents from 30 clusters determined through probability proportional to cluster size (PPS). The results showed that compliance to filariasis’ MDA in the working area of the Jetak Public Health Center in Semarang Regency was 78.6%. Characteristics of respondents who tend to be obedient in taking drugs are: respondents in the age group 26-45 years (82.6%), men (80.5%), graduated from junior high school (89.5%), working (81.5% ), have a good level of knowledge of filariasis (84.6%) and MDA (91.6%), have positive perceptions of susceptibility (84.9%), severity (84.0%), and benefits (90.4%), have negative perception of barriers (91.5%), received cadre support (91.7%) and social support (88.9%), and have experiences in side effects of the drugs in the first round (93.8%). Increased socialization is needed related to filariasis and MDA so that public compliance in filariasis’ MDA increases.